Inclusion of initial powder distribution in FEM modelling of near net shape PM hot isostatic pressed components. (September 2014) - Van Nguyen, C.; Bezold, A.; Broeckmann, C.
<x content-type="archive" xml:space="preserve">Abstract</x> The final shape of powder metallurgy hot isostatic pressing (HIP) components is determined by many factors, including the shape and size of the capsule, the initial density distribution of the powder before HIP, and HIP process parameters. Current HIP simulation, which usually assumes that the powder inside the capsule is homogeneous, cannot predict non-uniform shrinkage. Therefore, the purpose of this work is to develop a methodology to quantitatively determine the initial powder density distribution inside HIP capsules, which were precompacted by different techniques. The relative density distribution obtained from experimental work is used as the initial condition for numerical simulations. The final shapes of the capsules produced by HIP are compared to simulation results. The paper shows the sensitivity of the final shape on the initial powder density distribution and illustrates the need to implement the initial powder distribution into the finite element model to improve the quality of the near net shape HIP simulation.